2016
DOI: 10.1016/j.rboe.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the medial patellofemoral ligament by means of the anatomical double-bundle technique using metal anchors

Abstract: ObjectiveTo evaluate double-bundle reconstruction of the medial patellofemoral ligament (MPFL) using a graft from the semitendinosus tendon and fixation with metal anchors over the medium term.MethodsThis was a prospective cross-sectional study. After approval from the research ethics committee, 31 patients with patellofemoral instability who underwent MPFL reconstruction by means of the anatomical double-bundle technique, with fixation using metal anchors, were analyzed between May 2010 and January 2015. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 43 publications
2
27
0
1
Order By: Relevance
“…Administration of the Kujala questionnaire at the 2-year mark in our study demonstrated an average score of 89.20 (range: 78.95–99.45). This result compares favorably with the literature, which reports similar scores 2–2.5 years post-surgery of 73.40 [ 19 ], 80.90 [ 20 ], 86.00 [ 15 ], 87.00 [ 14 ], 89.20 [ 21 ], 91.40 [ 22 ], 92.00 [ 23 ], 94.03 [ 24 ], 94.69 [ 16 ] and 99.69 [ 18 ].…”
Section: Discussionsupporting
confidence: 85%
“…Administration of the Kujala questionnaire at the 2-year mark in our study demonstrated an average score of 89.20 (range: 78.95–99.45). This result compares favorably with the literature, which reports similar scores 2–2.5 years post-surgery of 73.40 [ 19 ], 80.90 [ 20 ], 86.00 [ 15 ], 87.00 [ 14 ], 89.20 [ 21 ], 91.40 [ 22 ], 92.00 [ 23 ], 94.03 [ 24 ], 94.69 [ 16 ] and 99.69 [ 18 ].…”
Section: Discussionsupporting
confidence: 85%
“…We compare the clinical results to other studies with the same technique [33][34][35][36][37][38][39] (►Table 5). All of the studies used the Kujala score, then most of them used the Lysholm score, some of them used the Tegner score.…”
Section: Discussionmentioning
confidence: 99%
“…Paxton et al 51 recommended using a combination of knee-specific surveys such as the Kujala or Lysholm scores in addition to the Tegner activity score to provide more complete information regarding the patient's knee function. Ideally, surveys should include more sport-specific criteria such 5 1 0 N/A 1 Astur et al 6 1 0 N/A 1 Becher et al 8 0 0 N/A 0 Bitar et al 9 1 0 N/A 1 Calanna et al 13 1 0 N/A 1 Camp et al 14 0 0 N/A 1 Carnesecchi et al 15 1 0 N/A 1 Christiansen et al 16 0 0 N/A 1 Deie et al 18 1 0 N/A 1 Drez et al 19 1 1 0 1 Ellera Gomes 20 1 0 N/A 1 Ellera Gomes et al 21 1 0 N/A 1 Feller et al 22 0 1 0 1 Fink et al 23 1 0 N/A 1 Gomes 25 0 0 N/A 1 Goyal 26 0 0 N/A 1 Han et al 27 1 0 N/A 1 Harle et al 28 0 1 0 1 Hinterwimmer et al 30 1 0 N/A 1 Howells et al 31 0 0 N/A 1 Kumahashi et al 32 1 0 N/A 1 Li et al 33 1 0 N/A 1 Lin et al 34 1 0 N/A 1 Lippacher et al 35 1 0 N/A 1 Ma et al 36 0 1 0 1 Mariani et al 39 0 0 N/A 1 Matsushita et al 40 0 0 N/A 0 Matthews and Schranz 41 1 0 N/A 1 Mulliez et al 45 1 0 N/A 1 Nomura and Inoue 47 1 0 N/A 1 Nomura et al 48 1 0 N/A 1 Panni et al 50 1 0 N/A 1 Petri et al 52 0 0 N/A 1 Raghuveer and Mishra 54 0 1 0 1 Ronga et al 56 1 0 N/A 1 Sadigursky et al 57 1 0 N/A 1 Slenker et al 59 1 0 N/A 1 Song et al 61 1 0 N/A 1 Steiner et al 62 0 1 0 1 Suganuma et al 63 1 0 N/A 1 Tompkins et al…”
Section: Discussionmentioning
confidence: 99%